Bilateral Chylhotorax after Falling from Height - Vildan Akpinar; Fulya Yilmaz Duran; Elif Duman; Murat Yasar Özkalkanli; Özgür Duran; Burcu Horsanali (Case Reports in Surgery)
Chylothorax is accumulation of chyle in the pleural cavity due to disruption of the thoracic duct. The causes can be classified as neoplastic, traumatic (iatrogenic or noniatrogenic), congenital, sporadic, spontaneous, and miscellaneous. A 22-year-old man with no feature in his history and family history was referred to emergency department with the case of falling from height. Abdominal computed tomogram (CT) revealed laceration of liver, grade 5 splenic laceration, fracture of the left acetabulum, and dislocation of the left hip. He was optimized for emergency splenectomy and close left hip reduction. On the 2nd day of the operation, bilateral chylotorax revealed. The treatment depends on its etiology, the amount of drainage, and the clinical picture. Treatment can be classified into 3 categories treatment of the underlying condition, conservative management (such as bed rest, nil by mouth or low fat medium chain triglycerides by mouth and total parenteral nutrition), and surgical management by ligation or clipping of the thoracic duct with open thoracotomy or video-assisted thoracoscopic surgery. The main purpose of surgical treatment is to stop the chylous leak.